2008
DOI: 10.1371/journal.pgen.1000298
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide siRNA-Based Functional Genomics of Pigmentation Identifies Novel Genes and Pathways That Impact Melanogenesis in Human Cells

Abstract: Melanin protects the skin and eyes from the harmful effects of UV irradiation, protects neural cells from toxic insults, and is required for sound conduction in the inner ear. Aberrant regulation of melanogenesis underlies skin disorders (melasma and vitiligo), neurologic disorders (Parkinson's disease), auditory disorders (Waardenburg's syndrome), and opthalmologic disorders (age related macular degeneration). Much of the core synthetic machinery driving melanin production has been identified; however, the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
143
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(149 citation statements)
references
References 41 publications
5
143
1
Order By: Relevance
“…Thus, a reasonable hypothesis for the observed otoconial abnormalities in Atg4b- and Atg5-null mice is that autophagy inhibition results in a transcriptional downregulation and thus instability of sorting complexes, which in turn leads to an impairment in otoconial matrix assembly and secretion and finally to otoconial abnormalities and balance disorders (Figure 8). Consistent with this model, an essential role for autophagy has been recently proposed in melanogenesis, another process for which the activity of Ap-3 and Bloc-1 sorting complexes is essential (51). The mechanism connecting autophagy disruption with the observed transcriptional alterations in sorting complexes is not clear.…”
Section: Discussionmentioning
confidence: 86%
“…Thus, a reasonable hypothesis for the observed otoconial abnormalities in Atg4b- and Atg5-null mice is that autophagy inhibition results in a transcriptional downregulation and thus instability of sorting complexes, which in turn leads to an impairment in otoconial matrix assembly and secretion and finally to otoconial abnormalities and balance disorders (Figure 8). Consistent with this model, an essential role for autophagy has been recently proposed in melanogenesis, another process for which the activity of Ap-3 and Bloc-1 sorting complexes is essential (51). The mechanism connecting autophagy disruption with the observed transcriptional alterations in sorting complexes is not clear.…”
Section: Discussionmentioning
confidence: 86%
“…Atg5 and Atg4B are involved in the secretion of otoconins by vestibular sensory cells of the inner ear [42]. Beclin1 and LC3-A have been implicated in the maturation of a specialized LRO, the melanosome [43]. As a novel LRO, the acrosome is regarded as a secretory lysosome not only because of its internal acid pH but also because it contains many enzymes associated with lysosomes in somatic cells [22].…”
Section: Atg7 Is Involved In Acrosome Biogenesismentioning
confidence: 99%
“…It has been reported that skin pigmentation is regulated by a variety of intrinsic and extrinsic factors [7,8] , as well as diverse signaling pathways including protein kinase A (PKA), phosphatidylinositol 3-kinase (PI3K), and mitogen-activated protein kinases (MAPKs) [9][10][11][12][13] . In particular, the MAPK kinase (MEK)/extracellular signal-regulated kinase (ERK) and the PI3K/Akt pathways have been shown to negatively regulate melanin synthesis in melanocytes and melanoma cells [14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%